Regulation Model of Religious Rights and Freedoms for Local Religious Believers in the Majapahit Constitution - Muwaffiq Jufri (Badan Strategi Kebijakan Hukum, 2022)
This article unfolds that the Majapahit Kingdom of Indonesian history has accommodated religious rights and freedom for local religious believers/adherents in its constitution. The kingdom was known in history as tolerant, harmonious, and had reasonable regulations to avoid faith-based conflicts. This finding is significant amid the rising concern over respect and protection of local indigenous religious beliefs in contemporary Indonesia. This research used normative legal methods with statutory, historical, and case approaches. The results and discussions were: first, the weakness of the Indonesian constitution's model of regulating religious rights and freedoms was that it closed access for local religious believers to adhere to and carry out their religious teachings; second, the model regulating the right to religious freedom for local religious believers needed to distinguish the status of religions in Majapahit. Local religions retain an equal position in the constitution. In addition, this constitution also guided religious believers in Majapahit as part of the regulations in the field of religious rights and freedoms. This research concluded that equalizing positions and concepts of spiritual development allows regulating religious rights and freedoms in its constitution to make Majapahit a tolerant, harmonious country that avoids faith-based conflicts.